Education for Sustainable Peace and Conflict Resilient Communities - Manojlovic, Borislava (Springer International Publishing, 2018)
This book articulates a practice and theory of education that aims to facilitate the emergence of sustainable peace and conflict-resilient communities in societies plagued by conflict. It does so by examining the agency of conflict-resilient communities and the dynamic processes of their interactions with larger societal structure. Although education is seen as a human right, the design of education policies, schooling models and curricula has primarily been the prerogative of elites, be they governments, academics or international actors. This book argues for a different approach to education, contending for more inclusivity and open deliberation in modeling education frameworks. Drawing on case studies and interviews with practitioners, scholars, activists, and policymakers, it applies the lenses of conflict resolution to a variety of education issues within fragile societies. .